1987
DOI: 10.1289/ehp.8772283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on metabolic events in the lung.

Abstract: Nicotine and cigarette smoke extract show acute physiological effects: increasing tracheal pressure (PTR), pulmonary artery pressure (PPA), systemic blood pressure (PyT), and left atrium pressure (PLA); and decreasing cardiac output (4AORTA) and blood flow to the left lower lobe (1L). In addition, cigarette smoking induces bronchoconstriction, thus decreasing peak flow, FVC, and FEVY.o in healthy subjects. It has also been demonstrated that cigarette smoking caused temporary slowing of mucociliary clearance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 79 publications
0
9
0
2
Order By: Relevance
“…Several studies have observed that angiotensin II promotes inflammation and tissue injury, mediating key events in animal models of autoimmune disease (Marchesi, Paradis, & Schiffrin, 2008; Okunuki et al., 2009; Platten et al., 2009; Sagawa, Nagatani, Komagata, & Yamamoto, 2005; Stegbauer et al., 2009). Based on previous observations demonstrating that serum ACE activity increases significantly after smoking (Kitamura, 1987) and chronic smoking results in enhanced RAS activation in monozygotic twins, discordant for smoking (Laustiola, Lassila, & Nurmi, 1988), Correale and Farez (2015) (Correale & Farez, 2015) recently investigated whether RAS might be involved in immunomodulatory effects of smoking on MS progression. As expected, their findings argue in favor of smoking having modulator role in the expression and activity of RAS components: both auto‐reactive T‐lymphocytes and monocytes derived from patients who smoked produced significantly higher amounts of renin, ACE, as well as angiotensin II receptor type I (AT1R).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed that angiotensin II promotes inflammation and tissue injury, mediating key events in animal models of autoimmune disease (Marchesi, Paradis, & Schiffrin, 2008; Okunuki et al., 2009; Platten et al., 2009; Sagawa, Nagatani, Komagata, & Yamamoto, 2005; Stegbauer et al., 2009). Based on previous observations demonstrating that serum ACE activity increases significantly after smoking (Kitamura, 1987) and chronic smoking results in enhanced RAS activation in monozygotic twins, discordant for smoking (Laustiola, Lassila, & Nurmi, 1988), Correale and Farez (2015) (Correale & Farez, 2015) recently investigated whether RAS might be involved in immunomodulatory effects of smoking on MS progression. As expected, their findings argue in favor of smoking having modulator role in the expression and activity of RAS components: both auto‐reactive T‐lymphocytes and monocytes derived from patients who smoked produced significantly higher amounts of renin, ACE, as well as angiotensin II receptor type I (AT1R).…”
Section: Discussionmentioning
confidence: 99%
“…This increase, however, was not sustained after repeated 10-day exposure, indicating a time-or exposure (acute vs. chronic)-dependent effect (7). In healthy human volunteers, serum ACE activity showed a significant increase immediately after smoking and returned to control level 20 min after smoking (80). Increased serum ACE levels were also found in dogs after exposure to cigarette smoke or intravenous nicotine infusion (126).…”
Section: Nicotine and The Ras In The Lungmentioning
confidence: 99%
“…Studies in laboratory animals support the activation of RAS by cigarette smoke or nicotine. Chronic nicotine administration through osmotic minipumps has been shown to elevate plasma renin activity in rats subjected to a high-salt diet (120), and cigarette smoke and/or nicotine administration increase plasma ACE activity with increased conversion of ANG I to ANG II (7,80,126).…”
Section: Nicotine and The Ras In Cardiovascular Dysfunctionmentioning
confidence: 99%
“…Aktivitas angiotensin converting enzim (ACE) juga meningkat dan kembali ke kontrol dalam dua puluh menit. [30][31][32][33] Patogenesis rokok dalam hubungannya dengan peninggian tekanan arteri pulmonal diinvestigasi oleh Wright 18,19 Barutcu et al 15 juga melaporkan dari 20 perokok yang dievaluasi dengan Doppler serta tricuspid inflow and early and late velocity didapatkan penurunan indeks performa ventrikel kanan sebelum dan 30 menit sesudah merokok.…”
Section: Mekanisme Khusus Gangguan Ventrikel Kananunclassified